The Impact of Supply Chain Digitalization on the Resilience of New Retail Enterprises: Mechanisms and Evidence - Hao, Xiong; Song, Wenqian (Journal of Global Economy, Business and Finance, 2026)
This study utilizes panel data from Shanghai and Shenzhen A-share new retail listed companies in China (2013–2023) to investigate the direct effects and mechanisms of supply chain digitalization on new retail enterprises. Results show that supply chain digitalization significantly enhances enterprise resilience, with robust effects. Mediation analysis reveals that it indirectly improves resilience through better product market performance. Additionally, enterprise ownership characteristics moderate the impact, with non-state-owned enterprises exhibiting a higher response to supply chain digitalization.